Unraveling Novel Biosynthetic Gene Clusters from the Siwa Oasis Microbiome - Ajagbe, Muhammad Adeyemi (AUC Knowledge Fountain, 2025)
The growing demand for novel therapeutics—such as antimicrobial, anticancer, and anti-inflammatory agents—underscores the need to explore new avenues for pharmaceutical discovery. Microbial communities serve as invaluable reservoirs of bioactive compounds encoded by biosynthetic gene clusters (BGCs). However, traditional natural product discovery faces significant challenges, including the inability to culture most microorganisms and the frequent rediscovery of known metabolites. Sequence-based metagenomics offers a transformative approach, enabling the rapid identification of BGCs directly from environmental samples. In this study, NovaSeq-6000 shotgun sequencing was employed to investigate the biosynthetic potential of microbial communities in Cleopatra and Fatnas Springs, two unique freshwater hot springs in the Siwa Oasis. These springs harbor diverse microbes dominated by bacteria (~99%), with a negligible representation of archaea (< 0.01%). Taxonomic analysis revealed a community primarily composed of mesophilic bacteria in the phyla Pseudomonadota, Bacteroidota, Actinomycetota, and Planctomycetota, collectively accounting for ~93% of the microbial population. The integrated bioinformatics pipeline used reconstructed 37 medium-to-high quality metagenome-assembled genomes (MAGs), half of which were phylogenomically related to genomes from other freshwater ecosystems. Moreover, a total of 147 BGCs was identified, predominantly from MAGs in the phyla Pseudomonadota, Actinomycetota, and Acidobacteriota. While Cleopatra Spring exhibited a higher prevalence of BGCs potentially producing terpenes, followed by ribosomally synthesized and post-translationally modified peptides (RiPPs), Fatnas Spring showed greater richness in RiPPs-associated BGCs. Remarkably, 100% and 96.6% of these BGCs were deemed novel compared to the MiBIG and BGC Atlas databases, respectively. These findings underscore Siwa Oasis as a promising reservoir for natural product discovery and emphasize the capacity of the untapped biosynthetic potential of unique ecosystems in addressing global health crises.